SPACES OF EUROPEANISATION IN THE BALKANS cities, networks and urban epistemic communities. - Pajvanc??ic??-Cizelj, Ana (Southeast European studies, 2026)
This book tackles the spatial dimension of Europeanization in the Balkans by focusing on cities, inter-urban networks, and urban epistemic communities.Exploring the participation of urban actors from the Balkans in 18 European inter-urban networks, it employs a new mixed-method framework to show how such participation continuously reshapes Balkan Cities' urban trajectories with contradictory and variegated consequences. Against the backdrop of the existing state and conflict-centred literature on (failures) of European integration in the region, the author offers a fresh perspective on Europeanization as it unfolds through direct inter-city cooperation.This volume will be of interest to both scholars of urban studies and Southeast European Studies, as well as anyone interested in the Europeanization of the Balkans and its cities.